BILATERAL ULTRASOUND-GUIDED ABDOMINAL PERIPHERAL BLOCK IN TAP PLANE, TAP - BLOCK - M. Sekulovski; B. Simonska; G. Mutafov; V. Alexandrov; L. Spassov (Trakia Journal of Sciences)
INTRODUCTION: Bilateral ultrasound-guided peripheral block (TAP - block) in the plane between the inner oblique abdominal muscle and the transversal abdominal muscle – TAP plane, is a regional anesthesia technique by infiltration of a local anesthetic, provides analgesia for operations involving the anterior abdominal wall. The analgesic effectiveness of the block decreases the consumption of opioid analgesics and non-steroidal anti-inflammatory drugs. AIM: In this study, we evaluated the intraoperative analgesic efficacy of bilateral TAP - block and the consumption of opioid analgesics in patients undergoing bilateral laparoscopic inguinal hernia repair. METHODS: The study was conducted with 35 patients, who were randomized into two groups. In the control group (group I), there are patients who received general anesthesia (GA), and experimental group (group II), were patients who have received general anesthesia and a bilateral tap block (GA + TAP). RESULTS: Patients with TAP-block (group II) have significantly lower fentanyl consumption compared to group I. CONCLUSION: Multimodal approach for the simultaneous administration of general anesthesia with a TAP block provides effective intraoperative analgesia and significantly reduces the perioperative consumption of opioid analgesics.